Effects of temperature on anammox performance and community structure. (July 2018) - He, Shilong; Chen, Yi; Qin, Meng; Mao, Zhen; Yuan, Limei; Niu, Qigui; Tan, Xicheng
Highlights: Cold-tolerant anammox was acclimated successfully with temperature change. Adverse effects caused by low temperature (8 °C) could be restored. SAA of anammox acclimated at 23 °C on ex situ temperature (33 and 28 °C) was higher. Ca. Kuenenia was more abundant (55.18%) in the microbial community at 13 °C. Abstract: A lab-scale anammox up-flow anaerobic sludge blanket (UASB) reactor was run to investigate the influence of temperature on anammox performance and community structure. The anammox system had a higher substrate tolerance at 13 °C than at 18 °C. The adverse effects caused by the use of a lower temperature (8 °C) could be restored. The nitrogen removal rate (NRR) decreased with decreasing in situ specific anammox activity (SAA). Interestingly, the ex situ SAA acclimated at 23 °C, when exposed to ex situ temperatures of 33 and 28 °C, was higher than for those acclimated at 33 and 28 °C. No shift was observed in the optimum temperature for ex situ SAA in the whole lowering process of anammox UASB. More extracellular polymeric substances were produced in response to cooler conditions (18 °C and 13 °C). Ca. Kuenenia became much more abundant (55.18% of the microbial community) and had a competitive advantage over other anammox bacteria (AnAOB) at 13 °C.